2015
DOI: 10.1007/s12665-015-4178-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and health impact of potentially harmful elements distribution in the Panyam (Sura) volcanic province, Jos Plateau, Central Nigeria

Abstract: The Panyam volcanic province is a plateau covering a superficial area of about 1200 km 2 , dotted by a number of dormant volcanoes forming prominent landmarks above the host continental gneiss-migmatite-granite rocks and stretching for about 12 km. The volcanism is basaltic, characterized by alkaline-calc-alkaline compositions. Large population of people live and depend on the volcanic environment for potable water and agriculture, most of whom display various forms of health problems ranging from dental carie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The evidence in these countries is mostly from surveys and published case reports. There was moderate evidence of presence in Equatorial Guinea and Nigeria; the evidence in Equatorial Guinea was based on a survey conducted in 1988[2, 40], whereas the evidence in Nigeria is based on a case report in 2015[41]. In addition, both WHO and Price indicated the presence of podoconiosis in Equatorial Guinea and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence in these countries is mostly from surveys and published case reports. There was moderate evidence of presence in Equatorial Guinea and Nigeria; the evidence in Equatorial Guinea was based on a survey conducted in 1988[2, 40], whereas the evidence in Nigeria is based on a case report in 2015[41]. In addition, both WHO and Price indicated the presence of podoconiosis in Equatorial Guinea and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…None of such adverse effects associated with farming on these soils could for instance be found in the Plateau of the Rio Grande do Sul or in the Sabzevar Range. In the Panyam Province, health issues were mainly associated with more mobile and often unregulated TE such as selenium (Lar & Gusikit, 2015). Conversely, in basaltic Xuyi County in eastern China, Wang et al (2020) reported nickel accumulations in crop grains beyond national food safety recommendations associated with ingestion health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Many volcanic soils exceed indeed the legal limits presented in this study. In the basaltic Panyam province of Nigeria for instance, the nickel content in soils ranges between 89 and 411 ppm (Lar & Gusikit, 2015). In the basaltic Plateau of the Rio Grande do Sul (Brazil), soils display an average copper content of 101 ppm (Althaus et al, 2018) while the basaltic-derived soils from the Sabzevar Range in Iran contain between 85 and 109 ppm copper, 149-153 ppm nickel and 154-183 ppm chromium (Mazhari et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations